THE LEGAL AND ETHICAL ASPECTS OF ORGAN DONATION: BETWEEN ALTRUISM AND (DIS)TRUST - Čović, Ana; Knežević Bojović, Аna (Serbian political thought, 2025)
The Republic of Serbia is last on the list of European countries and among the last in the world when it comes to the number of performed transplants. This paper will provide an overview of the relevant legal regulations and challenges facing everyone who needs an organ transplant after the Constitutional Court of the Republic of Serbia found the provisions of Article 23 of the Law on Human Organ Transplantation from 2018, which refer to organ donation from a deceased individual, and the provisions of Article 28 of the Law on Human Cells and Tissues, which stipulate the conditions for tissue donation, to be unconstitutional, and citing religious standpoints on this current legal, medical, and bioethics issue. In addition, the COVID-19 pandemic saw a decrease in the number of donated and transplanted organs, while the post-COVID period saw the frequent occurrence of issues of distrust of the healthcare systems and the World Health Organization among different segments of the population, and thus the impact of this (dis)trust on the decision of individuals to become potential donors, especially in countries facing a high level of corruption in all areas, as well as war-torn areas where the possibility for unsanctioned human organ trade on the black market is high. It is the authors’ conclusion that war conflicts, the (lack of a) clear and complete legal framework, and the level of trust in state and healthcare institutions, have a direct impact both on the number of donors and the transplants performed in a country.
Keywords: organ donation; bioethics; the Republic of Serbia; EU law; organ trade